Meeting of Evaluation Advisory Committee on 27-06-1995 Agenda Material - Planning Commission (Planning Commission, 1995)
Since first Five Year Plan, the funds have been provided in state budgets for provision of drinking water supply in the rural areas. In spite of the efforts by the States, it was observed during mid sixties that Rural Water Supply Schemes were implemented only in the easily accessible villages neglecting hard core rural areas. The Government of India, therefore, requested the States to identify such villages as problem villages so that efforts could be directed towards tackling clearly identified problem villages.
Planning Commission Programme Evaluation Organisation
Planning Commission Programme Evaluation Organisation